Reflections on the 2013 Decade Award—“Exploitation, Exploration, and Process Management: The Productivity Dilemma Revisited” Ten Years Later - Benner, Mary J.; Tushman, Michael L. (Academy of Management Review, 2015)
This article reflects on our 2003 article, “Exploitation, Exploration, and Process Management: The Productivity Dilemma Revisited,” which received the Academy of Management Review’s Best Article Award in 2003 and Decade Award in 2013. We consider the context within which we wrote the original article, with particular reference to the theoretical, empirical, and managerial problems salient at that time, and comment on the likely reasons the article has had a sustained influence in the field. Looking forward, we first ask whether the paradoxes and inconsistencies we discussed are still fundamental organizational challenges, and then go further to consider ways the domain of innovation itself has changed. We suggest that because of fundamental shifts in communication and information processing costs and the increasing modularity of products and services, the nature and locus of innovation have changed over the past decade. These secular trends have profound implications for our theories of innovation and organizations. Our extant theory and research are increasingly uncoupled from the phenomena. We would be well served to revisit the nature, locus, and basic processes of innovation.